Discussion about math, puzzles, games and fun. Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ π -¹ ² ³ °

You are not logged in.

- Topics: Active | Unanswered

**jadewest**- Replies: 4

Hello,

I can't solve this exercise.

In an earthquake, a Seismic wave travels through the Earth layer, which gives out an energy that causes the earth to shake and also gives out low frequency acoustic energy. The instrument seismograph is based on a logarithmic scale, called the Richter Scale. Since it’s a base 10 scale each number increase on the scale indicates an intensity 10 times stronger than the previous number on the scale.

The Midlands of South Carolina have been experiencing a “swarm” of earthquakes in recent months. The strongest registered 3.7 on the Richter Scale. If the smallest recorded during the swarm was 2.7, what is the mathematical relationship between the two recorded earthquakes? Explain.

Thank you,

Jade

Hello,

I have completed these exercises about finding the domain and range. Are they correct?

3. y = 20 - 2x^2

Domain: (-∞, +∞)

Range: (-∞, 20)

4. y = 25(-7x-4)^64

Domain: (-∞, ∞)

Range: (0, ∞)

Thank you so much,

Jade

**jadewest**- Replies: 6

Hello,

I can't solve this exercise.

What is the domain and range of the function:

y = x^2 / (x^2-16)

Thank you so much,

Jade

**jadewest**- Replies: 1

Hello,

I need help with these two exercises.

3 If y varies directly as x and z and y is 5 when x is 3 and z is 4, find y when x is 2 and z is 3. Show steps,

Direct => y = kx

5 = k*3

5/3 = (k*3)/3

k = 5/3

y = (5/3)x

y = (5/3)*2

y = 10/3 = 3.333...

Direct => y = kz

5 = k4

5/4 = (k*4)/4

k = 5/4

y = (5/4)z

y = (5/4)*3

y = 15/4 = 3.75 (HOW DO I NOT LOSE Z?)

9 If w varies directly with f and inversely with g and w = 5 when f = 2 and g = 7, find w when f = 4 and g = 9.

Direct => w = kf

5 = 2k

k = 5/2 = 2.5

w = 2.5 * 4

w = 10

Inverse => w = k/g

5 = k/7

k = 7*5 = 35

w = 35/9 = 3.888...9 (HOW DO I NOT LOSE G?)

Thank you so much,

Jade

Hello,

Does this look correct considering the feedback in the parenthesis?

10. Dwight will be celebrating his 7th birthday with a swimming party that his parents are planning for him. The facility rents for $500 plus $25 per guest including lunch and drinks. How many guests can they invite if their budget is $2500?

(Show the equation substituting into y and then how to solve the equation for x)

y = mx + b

y = 25x + 500

2500 = 25x + 500

25x = 2000

x = 80 guests

Hello,

I have one last exercise I need to check if it is correct.

Dwight will be celebrating his 7th birthday with a swimming party that his parents are planning for him. The facility rents for $500 plus $25 per guest including lunch and drinks. How many guests can they invite if their budget is $2500?

2500 - 500 = 2000

2000/25 = 80 guests

Thank you for your help,

Jade

Hello,

Thank you so much for your detailed explanation!

This is what I came up with f(g(x)) for exercise 8.

f(g(x))= f (-5x + 3) = -1/5 (-5x + 3) + 3/5 =

(After that I am stuck and don't know how to get x as the result.)

This is the result for f(g(x)) for exercise 9.

f(g(x))= f (x -1/2) = x - 1/2 + 1/2 = x - 0 = x

(IS THIS CORRECT?)

Jade

Hello,

Thank you for your help! This is what the teacher is telling me about how to do these exercises.

Step 1 Find f(g(x)).

Step 2 Find g(f(x)).

Step 3 If both Step 1 and Step 3 have x as the result, then they are inverses.

The problem is that I can't solve the first two steps for exercises 8 and 9.

Jade

**jadewest**- Replies: 11

Hello,

I can't solve these two exercises.

C Are f and g inverses of each other? Support your response algebraically.

8 f(x) = -(⅕)x + (⅗), g(x) = -5x + 3

9 f(x) = x + ½, g(x) = x - ½

Thank you so much,

Jade

**jadewest**- Replies: 1

Hello,

I can't figure out what the domain for this exercise is for days. Can someone help me?

7 f(x) = 2x + 3 and g(x) = –x^2 + 5, find (g o g) (x).

(g o g) (x) = g (g(x))

= g (-x^2 + 5)

= (- (-x^2 + 5) ^2 + 5)

= (-(-x^2 + 5) (-x^2 + 5) + 5)

= (- (x^4 -10x^2 + 25) + 5)

= -x^4 + 10x^2 - 20

Thank you,

Jade

**jadewest**- Replies: 2

Hello,

Can I get feedback on if these look correct?

1 Given f = { (-1, 8), (3, -1), (-2, 0) } and g = { (-5, 8), (3, -1), (-1, 0) } . Find (f o g)(3). Show steps,

( f o g)(3) = f ( g(3) ) = f(-1) = 3 (IS THIS CORRECT?)

2 Given f = { (-1, 8), (3, -1), (-2, 0) } and g = { (-5, 8), (3, -1), (-1, 0) } . Find (g o f)(3). Show steps,

( g o f)(3) = g ( f(3) ) = g(-1) = 3 (IS THIS CORRECT?)

5 f(x) = 15x -12 and g(x) = -15x^2 + 14x - 10, find (f o g)(-1).

( f o g)(-1) = f ( g(-1) )

g(-1) = -15^2 + 14(-1) - 10 = -249

f(-249) = 15(-249) - 12 = -3747

(f o g)(-1) = -3747 (FOR THIS ONE I WAS TOLD THAT -15 IS NOT SQUARED, BUT IN THE G FUNCTION IT IS SQUARED. WHAT AM I SUPPOSED TO CHANGE?)

Is it supposed to be done like this:

(f o g)(-1) = f( g(x))

f( -15^2 + 14x - 10)

15x ( -15^2 + 14x - 10) - 12

-3375x + 210x^2 -150x - 12

= 210^2 -3525x - 12

6 f(x) = -13x2 -13x + 14 and g(x) = -13x - 11, find (g(g(-3)).

(g o g)(-3) = g ( g(-3))

= g ( (-13x - 11) )

= -13 (-13x - 11) -11

= -169x + 143 - 11

= 169x + 132 (THE FEEDBACK WAS THAT FIRST, g(-3)) PUT -3 IN THE G FUNCTION AND THEN SIMPLIFY)

Is it supposed to go like this:

(g o g)(-3) = g ( g(-3))

g(-3) = -13(-3) -11 = 28

(g o g)(-3) = 28

7 f(x) = 2x + 3 and g(x) = –x^2 + 5, find (g o g)(x).

(g o g)(x) = g (g(x))

= g (-x^2 + 5)

= √(-x^2 + 5)

= -x + 5 Domain: {x:x Ð„ R} (I WAS TOLD THAT THE RADICAL SHOULDN'T BE THERE. HOW DO I SOLVE THIS?)

8 f(x) = x + 3 and g(x) = √x, find g(f(x)).

(g o f)(x) = g ( f(x))

= g (x + 3)

= √(x + 3) Domain: {x: x ≤ 3} (IS THIS CORRECT?)

9 f(x) = x - 1 and g(x) = 3/(x-1), find f(g(x)).

(f o g)(x) = f (g(x))

= f [ 3/ (x - 1) ] Domain: {x: x ≥ 1} (IS THIS CORRECT?)

FOR THE FOLLOWING EXERCISE I HAVE SOLVED PARTS A AND B, BUT AM TOLD THAT THE ANSWER FOR PART C IS NOT ENOUGH.

10 You go to a local mechanic to get your tires changed. The tires cost x dollars. There is a 6% sales tax, but you get a 10% discount.

A Write a function t(x) for the total purchase amount after taxes but before discounts and fees.

Function with no discount and fees:

tax: 6%

tire cost: x

t(x) = x + 6% of x

t(x) = x + 0.06x

t(x) = 1.06x

B Write a function d(x) for the total after discounts on purchase amount x but before taxes and fees.

Function with no taxes and fees:

When discount is given after tax, then 10% is deducted from the original cost of the tire:

d(x) = x - 0.10x

C Does it make a difference in the total price whether the mechanic adds the tax first d(t(x)) or takes the discount first t(d(x))? Do not replace x with a numerical value. Show the work to support your answer while keeping x in your work.

It does make a difference in the total price if discount is applied first. Out of the whole amount, you would pay 90% of what it costs. When taxes are added to the discounted price, then the total price would be way less than if the taxes were added first and then the discount.

Thank you so much,

Jade

**jadewest**- Replies: 0

Hello,

Can I get feedback on if these look correct?

1 Given f = { (-1, 8), (3, -1), (-2, 0) } and g = { (-5, 8), (3, -1), (-1, 0) } . Find (f o g)(3). Show steps,

( f o g)(3) = f ( g(3) ) = f(-1) = 3 (IS THIS CORRECT?)

2 Given f = { (-1, 8), (3, -1), (-2, 0) } and g = { (-5, 8), (3, -1), (-1, 0) } . Find (g o f)(3). Show steps,

( g o f)(3) = g ( f(3) ) = g(-1) = 3 (IS THIS CORRECT?)

5 f(x) = 15x -12 and g(x) = -15x^2 + 14x - 10, find (f o g)(-1).

( f o g)(-1) = f ( g(-1) )

g(-1) = -15^2 + 14(-1) - 10 = -249

f(-249) = 15(-249) - 12 = -3747

(f o g)(-1) = -3747 (FOR THIS ONE I WAS TOLD THAT -15 IS NOT SQUARED, BUT IN THE G FUNCTION IT IS SQUARED. WHAT AM I SUPPOSED TO CHANGE?)

Is it supposed to be done like this:

(f o g)(-1) = f( g(x))

f( -15^2 + 14x - 10)

15x ( -15^2 + 14x - 10) - 12

-3375x + 210x^2 -150x - 12

= 210^2 -3525x - 12

6 f(x) = -13x2 -13x + 14 and g(x) = -13x - 11, find (g(g(-3)).

(g o g)(-3) = g ( g(-3))

= g ( (-13x - 11) )

= -13 (-13x - 11) -11

= -169x + 143 - 11

= 169x + 132 (THE FEEDBACK WAS THAT FIRST, g(-3)) PUT -3 IN THE G FUNCTION AND THEN SIMPLIFY)

Is it supposed to go like this:

(g o g)(-3) = g ( g(-3))

g(-3) = -13(-3) -11 = 28

(g o g)(-3) = 28

7 f(x) = 2x + 3 and g(x) = –x^2 + 5, find (g o g)(x).

(g o g)(x) = g (g(x))

= g (-x^2 + 5)

= √(-x^2 + 5)

= -x + 5 Domain: {x:x Ð„ R} (I WAS TOLD THAT THE RADICAL SHOULDN'T BE THERE. HOW DO I SOLVE THIS?)

8 f(x) = x + 3 and g(x) = √x, find g(f(x)).

(g o f)(x) = g ( f(x))

= g (x + 3)

= √(x + 3) Domain: {x: x ≤ 3} (IS THIS CORRECT?)

9 f(x) = x - 1 and g(x) = 3/(x-1), find f(g(x)).

(f o g)(x) = f (g(x))

= f [ 3/ (x - 1) ] Domain: {x: x ≥ 1} (IS THIS CORRECT?)

FOR THE FOLLOWING EXERCISE I HAVE SOLVED PARTS A AND B, BUT AM TOLD THAT THE ANSWER FOR PART C IS NOT ENOUGH.

10 You go to a local mechanic to get your tires changed. The tires cost x dollars. There is a 6% sales tax, but you get a 10% discount.

A Write a function t(x) for the total purchase amount after taxes but before discounts and fees.

Function with no discount and fees:

tax: 6%

tire cost: x

t(x) = x + 6% of x

t(x) = x + 0.06x

t(x) = 1.06x

B Write a function d(x) for the total after discounts on purchase amount x but before taxes and fees.

Function with no taxes and fees:

When discount is given after tax, then 10% is deducted from the original cost of the tire:

d(x) = x - 0.10x

C Does it make a difference in the total price whether the mechanic adds the tax first d(t(x)) or takes the discount first t(d(x))? Do not replace x with a numerical value. Show the work to support your answer while keeping x in your work.

It does make a difference in the total price if discount is applied first. Out of the whole amount, you would pay 90% of what it costs. When taxes are added to the discounted price, then the total price would be way less than if the taxes were added first and then the discount.

Thank you so much,

Jade

Hello,

In this exercise I am told to try the three intervals again. What am I doing wrong?

Jade

**jadewest**- Replies: 2

Hello,

I have solved this exercise as follows:

x^2 + 49 < 14x

7^2 + 49 < 14(7)

49 + 49 < 98

98 < 98 X

This inequality is not true, because 98 is equal to 98.

What is there more to solve?

Thank you,

Jade

**jadewest**- Replies: 3

Hi,

Is this the correct way to solve this exercise:

Nathan is a product manager for a home security company. Through testing and focus groups, he has modeled the equation P = -(x - 32)^2 + 1000 to represent the profit (in thousands) of the price x for a new home security camera. Find the prices in dollars at which Nathan can make a profit of at least $471, 000. Show your work as it is done in the lesson content and include units of measurement.. HINT: Use 471 as part of the inequality you set up, not 471,000.

- (x - 32)^2 + 1000 = 471

1000 - 471 = (x - 32)^2

529 = (x - 32) (x -32)

529 = x (x - 32) - 32 (x - 32)

529 = x^2 - 32x - 32x + 1024

529 = x^2 - 64x + 1024

529 - (x^2 - 64x + 1024) = 0

529 - x^2 + 64x - 1024 = 0

-x^2 + 64x - 495 = 0

- (x^2 - 64x + 495) = 0

x^2 - 64x + 495 = 0

Using the quadratic formula I get the answers:

x = 9 or x = 55

First interval, x < 9, select x = 8

-8^2 + 64(8) - 495 ≥ 471

81 ≥ 471 FALSE

Second interval, 9 < x < 55, select x = 30

2325 ≥ 471 TRUE. x values in that interval are part of the solution

Third interval, x > 55, select x = 56

6225 ≥ 471 TRUE. x values in that interval are part of the solution

ANSWER: 9< x < 55 or x > 55

Is this correct?

**jadewest**- Replies: 1

Hello,

I can't understand how to solve this problem:

Nathan is a product manager for a home security company. Through testing and focus groups, he has modeled the equation P = -(x - 32)2 + 1000 to represent the profit (in thousands) of the price x for a new home security camera. Find the prices in dollars at which Nathan can make a profit of at least $471, 000. Show your work as it is done in the lesson content and include units of measurement.. HINT: Use 471 as part of the inequality you set up, not 471,000.

Jade

Hello,

I also have trouble completing this exercise:

-x^2 - 12x - 32 > 0

Thank you so much,

Jade

**jadewest**- Replies: 3

Hello,

I can't solve this problem:

Nathan is a product manager for a home security company. Through testing and focus groups, he has modeled the equation P = -(x - 32)2 + 1000 to represent the profit (in thousands) of the price x for a new home security camera. Find the prices in dollars at which Nathan can make a profit of at least $471, 000. Show your work as it is done in the lesson content and include units of measurement.. HINT: Use 471 as part of the inequality you set up, not 471,000.

Thank you so much,

Jade

**jadewest**- Replies: 1

Hello,

I need help with this exercise.

A ball is launched upward at a speed of 20 meters per second (m/s) from a 60-meter tall platform. The equation for the ball’s height (h in meters) at time t seconds after launch is h = -4.9t2 + 20t + 60. How long before the ball hits the ground?

Best,

Jade

Hello,

I'm having trouble finding the solution for this:

2x > -4y

**jadewest**- Replies: 4

Hello,

I am having trouble solving this system of inequalities and graphing it:

2x > -4y

4y - 2x < 8

Thank you,

Jade

Thank you for your answer!

I am having trouble with this exercise.

4. Which is a factor of 8x^2 + 4x - 24 when it is completely factored?

A. (2x + 3)

B. (x - 2)

C. (x + 2)

D. (x + 3)

**jadewest**- Replies: 6

Hello,

Is my answer correct?

3. Mark is cutting fence posts that are 48 inches tall to sell. He is permitted a 2 inch margin of error. Otherwise, he cannot sell the fence posts. What absolute value inequality models this situation?

A. |x - 48| ≤ 2

B. |x + 48| ≤ 2

C. |x - 2| ≤ 48

D. |x + 2| ≤ 48

The right one is alternative A.

Thank you,

Jade

Hello!

I am not understanding what I am doing wrong in question 3. Also in questions 4 and 7, how do they continue?

Thank you in advance,

Jade

Hi,

Do these look correct now?

Thank you!

2. x^9 + 1

(x^3)^3 + 1^3

x^9 + 1 = (x + 1) (x^2 - (x) (1) + 1^2)

(x + 1) (x^2 - x + 1) (x^6 - x^3 + 1)

3. 2m^4 - 2mn^3

2m

2m (m^3) - 2m (m^2 - n^3)

2m (m^3 - m^2 - n^3)

4. 3a^4 + 81a

3a

3a (a^3) + 3a (27)

3a (a^3 + 27)

3a (a^3 + 3^3)

6. a^4 + 1

This can be factored, and leads to the answer (a^2 + 1)^2 -2a^2

7. a^4 – 64

This can be factored with the difference of squares which leads to the answer: (a^2 + 2^3) (a^2 - 2^3)

9. x^3 + x^2 - x – 1

x^2 (x +1) - 1 (x + 1)

(x + 1) (x^2 - 1)

(x - 1) (x + 1)

(x - 1) (x + 1)^2